2004
DOI: 10.1001/archopht.122.6.897
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked High Myopia Associated With Cone Dysfunction

Abstract: Bornholm eye disease (BED) consists of X-linked high myopia, high cylinder, optic nerve hypoplasia, reduced electroretinographic flicker with abnormal photopic responses, and deuteranopia. The disease maps to chromosome Xq28 and is the first designated high-grade myopia locus (MYP1). We studied a second family from Minnesota with a similar X-linked phenotype, also of Danish descent. All affected males had protanopia instead of deuteranopia. Methods: X chromosome genotyping, fine-point mapping, and haplotype an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 34 publications
5
81
3
Order By: Relevance
“…Such a finding is present in Caucasian patients with NYX mutation (Jacobi et al 2002;Zeitz et al 2005) as well as patients with other diseases, such as X-linked myopia (Haim et al 1988;Young et al 2004;Zhang et al 2006) and CSNB2 (OMIM 300071). Functional analysis identified that retinal ON-pathway dysfunction is involved in CSNB1, CSNB2 and GRM6 mutations (Dryja et al 2005;Khan et al 2005;Langrova et al 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Such a finding is present in Caucasian patients with NYX mutation (Jacobi et al 2002;Zeitz et al 2005) as well as patients with other diseases, such as X-linked myopia (Haim et al 1988;Young et al 2004;Zhang et al 2006) and CSNB2 (OMIM 300071). Functional analysis identified that retinal ON-pathway dysfunction is involved in CSNB1, CSNB2 and GRM6 mutations (Dryja et al 2005;Khan et al 2005;Langrova et al 2002).…”
Section: Discussionmentioning
confidence: 91%
“…refractive error and propensity to develop further ocular complications, has allowed considerable progress in the study of myopia development. Two X-linked recessive forms of myopia/cone dysfunction and sole myopia have been identified (MYP1, OMIM 310460 and MYP13, OMIM 300613) on chromosome Xq28 (15,16) (23), and at chromosome 10q21.1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Based on genetic studies in families and/or unselected single patients with inherited myopia, up to 15 loci responsible for or involved in non-syndromic myopia have been mapped on human chromosomes to date. Despite the considerable number of recognized loci, no disease genes, either for Xchromosomal recessive ('MYP1' OMIM 310460, MYP13 OMIM 300613) (15)(16)(17) or autosomal dominant disease phenotypes (MYP2 OMIM 160700, MYP3 OMIM 603221, MYP4 OMIM 608367, MYP5 OMIM 608474, MYP11 OMIM 609994, MYP12 OMIM 609994, and myopia locating to chromosome 10q21.1) (18)(19)(20)(21)(22)(23)(24) have been identified. This also holds true for the genes involved in common myopia where six independent loci have been determined in the recent past (MYP6 OMIM 608908, MYP7 OMIM 609256, MYP8 OMIM 609257, MYP9 OMIM 609258, MYP10 OMIM 609259, and MYP14 OMIM 610320) (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,14] XLCD is a heterogeneous condition characterised by loss of colour vision, impaired visual acuity, macular atrophy and ERG …”
Section: X-linked Cone Photoreceptor Disordersmentioning
confidence: 99%
“…[1][2][3][4][5] These allelic X-linked cone opsin disorders display wide inter-and intrafamilial variability. However, in the majority the visual defect is non-progressive.…”
Section: Introductionmentioning
confidence: 99%